Extraction kinetics of fatty acids ethyl esters (FAEE) from oil phase using aqueous ethanol - Salina, Ahmad Safii (2015)
There is a need for alternative energy sources to replace petroleum based fuels due to the world’s crude oil reserves, global warming and environmental concerns. Biodiesel is clean, biodegradable, non-toxic and renewable fuel which is considered to be the best substitution for diesel fuel. In addition, biodiesel has more favourable combustion emission profile, such as low emissions of carbon monoxide, particulate matter and unburned hydrocarbons that make it suitable as alternative fuel in transportation sector. The main issue in biodiesel production is the expensive and non-stable supply of feedstock from vegetable oils. Alternatively, waste cooking oil, tallow and non-edible oils are favourable, although they are restricted feedstock for existing conventional productions of biodiesel due to its impurities such as food residue, biopolymer, cellular remaining, dissolved water and free fatty acids which necessitate additional acidic pre-treatments. The need of extension to the current biodiesel plants resulted in a pursuit of more viable process. One of the potential methods to produce biodiesel from low grade oils and cheap bioethanol is through the extractive reactor. Since, this technique is still new, many physical properties of the oil-alcohol mixture system were not explored. In particular, extraction kinetics of fatty acid ethyl esters from reactive region using aqueous ethanol is essential in order to determine the practicality of the process of extractive reaction for biodiesel synthesis. This experiment was conducted to characterize extraction kinetics of FAEE from oil phase by using aqueous ethanol and to determine the distribution coefficient of FAEE between oil phase and aqueous ethanol. Three different oil:ethanol molar ratio which is 1:1, 1:3 and 3:1 where oil was first diluted with FAEE was used with different stirred time range between 1-20min. A settling time for the mixture was recorded and a sample was taken for concentration determination using gas chromatography (GC) analysis. It is expected that the distribution coefficient of fatty acids ethyl esters (FAEE) is higher in solvent than solution.